A linear programming approach to the optimal utilization of renewable energy sources in buildings - Georgiou, Giorgos S.; Christodoulides, Paul; Georgiou, Avraam; Kalogirou, Soteris A. (My University, 2017)
Renewable Energy Sources (RES) have become an alternative form of energy in distribution networks. The 2010/31/EU Directive requires each new building to be highly energy efficient, with a large portion of its energy needs to be supplied by RES either locally or from a nearby source, from 2020 onwards. This paper emphasizes on the optimal utilization of the Photovoltaic (PV) energy produced in a building having PV panels and batteries installed. Following a brief introduction on the notion of the nearly Zero Energy Buildings (nZEB), a review regarding their energy optimization is made. The proposed model is then presented and discussed along with the real input data used. The optimization procedure chosen adopts a Linear Programming (LP) approach. The main aim of the proposed method is to ensure that the net grid energy is optimized through the use of the battery storage during the day, based on the forecasted PV generation and the forecasted demand. The results of a case study for a dwelling in Cyprus are discussed.
Keywords: Building energy management; Energy policy; Linear programming; Nearly zero energy buildings; Renewable energy optimization; Renewable energy sources